1968
DOI: 10.1038/bjc.1968.68
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free transmissible leukoses in Syrian hamsters, probably of viral aetiology

Abstract: IN an earlier communication we reported on multiple epithelial skin tumours in Syrian hamsters in which a Papova virus has been detected with great regularity, in large quantities, and in characteristic histological distribution, as evidenced by electron microscopic observation (Graffi et al., 1967). In experiments designed to transmit this disease by means of subcellular extracts from these tumours to other animals we surprisingly obtained in Syrian hamsters and, in certain circumstances, also in rats, leukos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1969
1969
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…The hamster papovavirus (HapV) has been isolated by Graffi et al from skin epitheliomas arising spontaneously in Syrian hamsters (Graffi et al, 1968). The tumors which are disseminated originate from the hair follicle epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…The hamster papovavirus (HapV) has been isolated by Graffi et al from skin epitheliomas arising spontaneously in Syrian hamsters (Graffi et al, 1968). The tumors which are disseminated originate from the hair follicle epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…24 Immunologic and biologic studies to establish the relationship between the helper virus reported in this paper and the indigenous hamster C-type virus(es)23' 24 are in progress. The other possible, but unlikely, sources of the helper virus is that it is a mutant of the input Gross leukemia virus or that it existed as a contaminent in the original virus stocks.…”
mentioning
confidence: 97%
“…Observations of over 300 normal breeding animals up to a year of age revealed a zero incidence of spontaneous tumors. This special strain or colony, however, was found to be particularly susceptible to cell-free transmission of a lymphoma virus derived from lymphomas induced in hamsters following inoculations of a recently discovered papilloma-inducing papovavirus of the hamster.s1 3 Apparently the susceptibility to induced-lymphoma expression exhibited by the special colony of hamsters is present in only some of the hamsters because the highest incidence of induced lymphomas observed seldom exceeded 50%.…”
mentioning
confidence: 97%